THE IMPORTANCE OF KNOWLEDGE IN INCREASING THE PERCEPTIONS OF THE EXTERNAL AUDITOR WHEN AUDITING FAIR VALUE ESTIMATES AND ITS REFLECTION ON THE EFFECTIVENESS OF PROFESSIONAL SKEPTICISM / AN ANALYTICAL STUDY OF IRAQI AUDITING FIRMS - Mohammed Ali Hussein; Asst. Prof. Dr. Iman Shakir Mohammed (American Journals, 2023)
The research aims to demonstrate the importance of knowledge and its impact on enhancing the external auditor's awareness when auditing fair value estimates, as it is reflected in improving the auditor's practice of professional skepticism. Among the findings of the research is that there is a statistical significance for external auditors in Iraq in their possession of technical knowledge of evaluation methods and that they have sufficient understanding of the activity of the economic unit in order to realize their responsibilities in identifying and evaluating the risks of material errors when auditing and exercising professional skepticism more effectively in order to achieve quality information in the auditor's report.
Keywords: knowledge, external auditor's perception, fair value. professional skepticism.